Singing Games - Jane Beethoven; Rosanne Emery; Synía Carroll-McQuillan (Music magic video library, 1995)
Viewers learn games that include music and movement - - See how children from other countries play singing games - - Respond to the rhythms of singing games - - Play along with a game from Africa.